Nontuberculous Mycobacterial Osteomyelitis of the Thumb: Successful Treatment with Serial Debridement, Antimicrobial Therapy, External Fixation, and Interphalangeal Arthrodesis. Issue 4 (October 2015) - Ehrlichman, Lauren K.; Kadzielski, John J.; Hyle, Emily P.; Jupiter, Jesse B.
Abstract : Case: We present the case of a fifty-seven-year-old woman treated for persistent inflammation of her thumb initially thought to be due to tuberculous osteomyelitis but which ultimately proved to be due to infection caused by a novel nontuberculous mycobacterial species. The establishment of this diagnosis and her treatment are described. Conclusion: Indolent hand infections caused by atypical mycobacterial species may occur even in immunocompetent hosts, and their diagnosis remains challenging and often elusive. Surgeons should have a low threshold of suspicion for nontuberculous mycobacteria in cases refractory to treatment by standard protocols. The miniature external fixator provides stability and allows for soft-tissue healing in the setting of hand infections.